2011
DOI: 10.1073/pnas.1109356108
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligase Nedd4 promotes α-synuclein degradation by the endosomal–lysosomal pathway

Abstract: α-Synuclein is an abundant brain protein that binds to lipid membranes and is involved in the recycling of presynaptic vesicles. In Parkinson disease, α-synuclein accumulates in intraneuronal inclusions often containing ubiquitin chains. Here we show that the ubiquitin ligase Nedd4, which functions in the endosomal–lysosomal pathway, robustly ubiquitinates α-synuclein, unlike ligases previously implicated in its degradation. Purified Nedd4 recognizes the carboxyl terminus of α-synuclein (residues 120–133) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
250
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(267 citation statements)
references
References 38 publications
(42 reference statements)
13
250
3
1
Order By: Relevance
“…4a). This finding is consistent with earlier research showing that Nedd4-1 promotes the endolysosomal sorting of aS for degradation (9). After washing off the medium, we did not detect re-secreted aS within 1 h, but a detectable amount of extracellular aS was observed up to 24 h (Fig.…”
Section: Lys-63 Linkage-specific Ubiquitination Enhances the Incorporsupporting
confidence: 82%
See 3 more Smart Citations
“…4a). This finding is consistent with earlier research showing that Nedd4-1 promotes the endolysosomal sorting of aS for degradation (9). After washing off the medium, we did not detect re-secreted aS within 1 h, but a detectable amount of extracellular aS was observed up to 24 h (Fig.…”
Section: Lys-63 Linkage-specific Ubiquitination Enhances the Incorporsupporting
confidence: 82%
“…2b, upper panel). This finding is contradictory to a report by Tofaris et al (9), which demonstrated that UbcH7 ubiquitinates aS together with Nedd4. This discrepancy could be due to different experimental conditions.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…Several studies have shown that ubiquitination plays an important role in regulating α-Syn degradation by the proteasome (39)(40)(41)(42)(43)(44). Interestingly, Tofaris et al (45) showed that ubiquitination of α-Syn by Nedd4 targets it for degradation via the endosomal/lysosomal pathway. However, the nature of the ubiquitination signal required for targeting α-Syn for proteasomal or lysosomal degradation remained unexplored.…”
Section: Resultsmentioning
confidence: 99%